ANALISIS PREFERENSI KONSUMEN TERHADAP KEPUTUSANPEMBELIAN BERAS PREMIUM DI RITEL MODERN (Indomaret dan Alfamart) KECAMATAN BELITANG MADANG RAYA KABUPATEN OKU TIMUR - Aisah; Anggi Fatmayati; Angellita Saputri (Jurnal Bakti Agribisnis, 2024)
Rice is a very important staple food in the world, including Indonesia. Indonesia is one of the countries with the highest rice consumption in the world, this is because rice has become a culture that cannot be separated from the Indonesian population. As a consumer product, rice depends a lot on whether many people will consume it. The more people consume rice, the higher the demand for rice. As Indonesia's population increases, demand for rice also increases. Although efforts have been made to reduce rice consumption through food diversification, the pace of development is still lower than the rate of population growth so demand for rice remains high. Modern retailers such as Indomaret and Alfamart which are found in several villages in the Belitang Madang Raya District make it easier for consumers to buy high quality rice because their presence has spread to the villages. Some are even open until 22.00 at night. The current public opinion is that people in the Belitang Madang Raya District buy quality rice from modern retailers because they already have names like Indomaret and Alfamart. This modern retail provides premium quality types of rice with various types and brands of premium rice and the arrangement of the products offered is complete, there are sales assistants providing good service, comfortable and safe facilities. The development of modern retail provides more alternatives for consumers to choose places to shop to meet their needs. This is what makes modern retail superior to others. Consumer preferences, in general, when making a purchase, will usually look at various aspects, especially the attributes of the product itself. In rice, several attributes are usually considered when buying rice, namely taste, color, size, cleanliness, aroma, price, where premium rice usually has quality that tends to be superior to all of these attributes, so it is not surprising that consumer preferences are more inclined towards premium rice compared to medium rice. However, with changes in policy regarding rice, it can indirectly cause changes in consumer behavior in purchasing rice. The objectives of this research are 1) To describe the characteristics of consumers who buy premium rice at the Modern Retail in Belitang Madang Raya District. 2) To describe the stages of the decision to purchase premium rice in modern retail in Belitang Madang Raya District. 3). To analyze consumer preferences for premium rice in modern retail in Belitang Madang Raya District. Results and discussion Characteristics of premium rice consumers in modern retail in Belitang Madang Raya District are consumers with an average age of 25 to 35 years, high school education level, 4 family members, self-employed and employees with an average income of ≥ Rp. 5,000,000. Stages of the decision process to purchase premium rice at modern retail in Belitang Madang Raya District, namely the reason for consuming it is due to health benefits and other factors such as price, easy to obtain and lifestyle. The benefit that consumers want is for their own consumption as a guarantee of guaranteed and quality nutrition. Consumers learn about premium rice from friends, family and advertisements, as well as places where purchases are made at Indomaret and Alfamart. Consumers consider buying premium rice because of the benefits of the product, and will buy other brands if premium rice runs out. Consumers buy premium rice in a planned manner, choose modern retail because it is close to where they live, and consider the price of premium rice commensurate with the quality and benefits. Consumers are satisfied while consuming premium rice. Consumer preferences for premium rice in modern retail in Belitang Madang Raya District are that consumers like affordable rice prices, premium rice that is clean, has a fragrant aroma, rice brands that are considered important, and consumer income is ≥ IDR 2,600,000. Then, of these five factors, the respondent's income is considered more important in influencing the decision to purchase premium rice because it has an importance value of 29.295% compared to other factors such as cleanliness, price, aroma and brand of rice. Based on the Pearson's R and Kendall's tau tests, an average value of 0.9125 or 91.25% was obtained, meaning that 91.25% of consumer preferences, namely income, cleanliness, price, brand and aroma, influence the decision to purchase premium rice and the remaining 8.75% is influenced by other variables not studied such as rice shape, rice color, rice taste, durability and packaging size. Thus, both tests are at a significant level. This means that there is a real and strong correlation between the conjoint results of consumer preferences, namely income, cleanliness, price, brand and aroma, with the decision to purchase premium rice in modern retail in Belitang Madang Raya District.